Multimodality : foundations, research and analysis : a problem-oriented introduction - Bateman, John; Wildfeuer, Janina; Hiippala, Tuomo (Mouton Textbook, 2017)
This textbook provides the first foundational introduction to the practice of analysing multimodality, covering the full breadth of media and situations in which multimodality needs to be a concern. Readers learn via use cases how to approach any multimodal situation and to derive their own specifically tailored sets of methods for conducting and evaluating analyses. Extensive references and critical discussion of existing approaches from many disciplines and in each of the multimodal domains addressed are provided. The authors adopt a problem-oriented perspective throughout, showing how an appropriate foundation for understanding multimodality as a phenomenon can be used to derive strong methodological guidance for analysis as well as supporting the adoption and combination of appropriate theoretical tools. Theoretical positions found in the literature are consequently always related back to the purposes of analysis rather than being promoted as valuable in their own right. By these means the book establishes the necessary theoretical foundations to engage productively with today's increasingly complex combinations of multimodal artefacts and performances of all kinds.